Multidimensional Risk Factors Drive Shoulder Musculoskeletal Disorders Among Construction Workers - Rizka Lailatul Rohmah; Baiduri Widanarko (FORIKES, 2026)
Shoulder musculoskeletal disorders are a persistent occupational health problem in the construction sector, arising from the interaction of physical, individual, psychosocial, and environmental demands. These conditions reduce functional capacity, impair work performance, and increase long‑term health burdens among construction workers. This study aims to synthesize evidence on the prevalence and multidimensional risk factors contributing to shoulder musculoskeletal disorders among construction workers, and to identify protective factors relevant for prevention. A narrative literature review was conducted using seven primary study that met predefined inclusion criteria. Evidence was extracted on worker characteristics, ergonomic exposures, psychosocial conditions, and environmental factors associated with shoulder pain. Findings were integrated to develop a comprehensive understanding of determinants influencing shoulder musculoskeletal disorders. The synthesis indicates that shoulder pain among construction workers is shaped by interconnected determinants. Individual factors such as elevated BMI, older age, and prolonged work experience increase vulnerability through heightened biomechanical strain and reduced recovery capacity. Physical and ergonomic exposures, including non‑ergonomic postures, repetitive arm movements, manual handling, high work speed, and heat strain consistently contribute to musculoskeletal overload. Psychosocial pressures, including stress and job dissatisfaction, amplify muscle tension and diminish coping ability, further worsening symptoms. Conversely, regular exercise emerges as a protective factor that enhances musculoskeletal resilience and reduces symptom severity. In conclusion, shoulder musculoskeletal disorders among construction workers are driven by multidimensional and cumulative risk factors. Effective prevention requires integrated interventions combining ergonomic improvements, safe‑work training, physical‑health promotion, and psychosocial support, with particular attention to high‑risk groups such as obese workers, older workers, and those with long occupational tenure.Keywords: shoulder pain; construction workers; ergonomic risk factors; psychosocial factors; occupational health; physical workload